THE INFLUENCE OF PRODUCT QUALITY AND E-WOM ON CUSTOMER PURCHASE DECISION AT ANJELA CAFE IN MINAHASA - Rezzonico, Alessandro; Pandowo, Merinda (Universitas Sam Ratulangi, 2025)
This study examines the influence of product quality and electronic word- of-mouth (E-WOM) on customer purchase decisions at Anjela Café in Minahasa. The food and beverage industry has evolved beyond fulfilling basic needs to offering experiences shaped by product quality and digital interactions. In this context, both product quality and E-WOM are essential in forming customer perceptions and driving purchasing behavior. This research uses a quantitative approach with data collected from 100 respondents through a structured questionnaire. Multiple linear regression analysis was applied to examine the simultaneous and partial effects of the independent variables. The findings reveal that product quality and E-WOM significantly influence customer purchase decisions, both simultaneously and individually. High product quality improves satisfaction and loyalty, while positive E-WOM enhances trust, reduces perceived risk, and strengthens brand image. These results underscore the importance for food service businesses, particularly small and medium-sized enterprises like Anjela Café, to maintain consistent quality and manage their digital reputation to improve customer decision-making and competitiveness in a rapidly evolving market. Keywords: Product Quality, Electronic Word of Mouth (E-WOM), Purchase Decision